Managing without leadership : towards a theory of organizational functioning - Lakomski, Gabriele (Elsevier, 2005)
Argues that leadership as traditionally understood does not explain organizational functioning. Drawing on coherentist epistemology, connectionism, and the theory of self-organizing dynamic systems, a naturalistic account of organizational functioning is explored that includes leaders as non-privileged agents in the fabric of organizational life.